2017
DOI: 10.15406/emij.2017.05.00125
|View full text |Cite
|
Sign up to set email alerts
|

STATINS-Do We Know Them or Are We Alice in Wonderland?

Abstract: Statins are a major cornerstone in preventing cardiovascular diseases. Evidence from Clinical trials have clearly indicated that statins are beneficial in the primary and secondary prevention of coronary heart disease. However, the overall benefits observed with statins appear to be greater than what might be expected from changes in lipid levels alone, suggesting effects beyond cholesterol lowering. Recent studies have clearly indicated that some of the cholesterol-independent or "pleiotropic" effects of stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For example, rosuvastatin is commonly prescribed to prevent cardiovascular complications and treat abnormal lipid levels in the blood. Although its high efficacy and safety profile as a drug to tackle dyslipidemia are well-known, multiple studies have reported dose-dependent adverse effects of prolonged statin therapy [15][16][17]. Ethnic differences exist in the pharmacokinetics of rosuvastatin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rosuvastatin is commonly prescribed to prevent cardiovascular complications and treat abnormal lipid levels in the blood. Although its high efficacy and safety profile as a drug to tackle dyslipidemia are well-known, multiple studies have reported dose-dependent adverse effects of prolonged statin therapy [15][16][17]. Ethnic differences exist in the pharmacokinetics of rosuvastatin.…”
Section: Introductionmentioning
confidence: 99%
“…Imposing regulation 2 is generally justified by the failure of markets to self-regulate and the literature explores how regulators and industry operate to resolve the failure (e.g. Bernstein, 1955; Stigler, 1971). It follows that economic benefits and the sustainability of markets rely upon both the regulator and industry ensuring the production of marketable goods.…”
Section: Introductionmentioning
confidence: 99%